2005
DOI: 10.1128/mcb.25.20.8960-8970.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hey Basic Helix-Loop-Helix Transcription Factors Are Repressors of GATA4 and GATA6 and Restrict Expression of the GATA Target Gene ANF in Fetal Hearts

Abstract: The Hey basic helix-loop-helix transcription factors are downstream effectors of Notch signaling in the cardiovascular system. Mice lacking Hey2 develop cardiac hypertrophy, often associated with congenital heart defects, whereas combined Hey1/Hey2 deficiency leads to severe vascular defects and embryonic lethality around embryonic day E9.5. The molecular basis of these disorders is poorly understood, however, since target genes of Hey transcription factors in the affected tissues remain elusive. To identify g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 59 publications
13
91
0
Order By: Relevance
“…This cross-transcriptional interaction prevents excessive heart growth and thus ensures an optimal mass for the embryonic heart. The ability of transcriptional repression and physical association of murine Hey2/Hrt2 with Gata4 has been shown to lie in the same basic domain (25,26). In our study, we have found that the Grl carboxyl region containing the Orange domain is required for physical association with Gata5, whereas the bHLH domain is critical for inhibiting the Gata5 transcriptional activity.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This cross-transcriptional interaction prevents excessive heart growth and thus ensures an optimal mass for the embryonic heart. The ability of transcriptional repression and physical association of murine Hey2/Hrt2 with Gata4 has been shown to lie in the same basic domain (25,26). In our study, we have found that the Grl carboxyl region containing the Orange domain is required for physical association with Gata5, whereas the bHLH domain is critical for inhibiting the Gata5 transcriptional activity.…”
Section: Discussionmentioning
confidence: 49%
“…Surprisingly, deletion of the carboxyl region, the putative Gata5 binding region, did not result in a complete loss of repressive activity. Because Hey2/Hrt2 protein does not affect repression through direct DNA binding (25)(26)(27), this result may be explained by the possibility that the bHLH domain might recruit other DNA-binding factors or Gata5-interacted proteins in HeLa cells that restore Grl repressive ability, but this may not occur in vivo and in cultured cardiomyocytes (Fig. 3M and SI Appendix, section VII).…”
Section: Grl Forms a Protein Complex With Gata5 And Represses Gata5-mentioning
confidence: 99%
“…Furthermore, HEY2-deficient embryos displayed a change in the expression patterns of GJA5, NPPA, and TBX5. 43,45,46 These genes have all previously been associated with AF. [47][48][49][50] Thus, several studies support our finding that BrS-associated genetic variants protect against AF.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous loss of GATA6 gene result in reduced expression of NKX2-5 gene [10]. In addition, Hey basic helix-loop-helix transcription factor 2 (Hey2), a downstream effector of Notch signaling, binds to GATA6 and directly represses ANF gene expression [52]. Mice lacking Hey2 develop VSD and cardiomyopathy [53].…”
Section: Discussionmentioning
confidence: 99%